(3cJGH JChjdGJ GdbQBfs - (3CHh efUhQ eMeO Hf eMeO Hf eMehO GdeGJQjOj,J (B333 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf bGd GdTjN CHh HcQ eMeO Hf CMeO GdSeQbfOi QMeg Gddg Ef cJGH GdJChjdGJ GdefShH Edi GdTjN GdGeGe CHh efUhQ deG JQjOi cJGH Ldjd GdeOO YXje GdaGFOI agj HjGf ePgH Cgd GdSfI s
(3BNQgG (B:s
(3jfJgi HJaSjQ bhdg JYGdi (B" (3MGaXG Ydi GdUdhGJ hGdUdGI GdhSWi hbhehG ddg bGfJjf (B" (3ef ShQI GdHbQI s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B335s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs